CLINICAL DECISION-MAKING MOMENTS: A REALITY FOR ADVANCE CARE PLANNING AT END-OF-LIFE. Issue 2 (1st June 2013) - Lee, S F; Beattie, J; O'Connor, M; Komessarof, P; Gold, M; Hunter, P
Abstract : Background: Decision-making at the end-of-life is complex and requires significant resources despite the presence of advance care plans. Questions often arise as to the meaning of an advance care plan, what constitutes such a plan and its legal status. Aims: This study aimed to examine issues influencing the decisions of people with advanced medical conditions. Methods: Case study methodology was used to inform the design of the study in two phases. Firstly, chart audits informed development of cases discussed in interviews. A purposive sample (n=20) with experience in advance care planning at end-of-life including health professionals, community leaders, patients and carers were interviewed. The study was conducted in a metropolitan health service. Results: Results indicate that advance care planning takes place in decision-making moments. The readiness of those involved in decision-making to either commence planning for end-of-life care or to implement a plan at end-of-life to provide for care needs were factors. End-of-life care planning and action occur in a context of difference (people, place and tensions). Discussion and Conclusions: This study suggests that, whether advance directives are available or not, towards the end of a patient's life, clinical decision-making is often in response to issues that may not have been predicted or discussed in the planning phase. Health professionals and family members may be ill-equipped to engage in discussions, despite the presence of an advance care plan. Policy, education and resources need to support the necessity for in the moment decision-making. Acknowledgement: This project was funded by the National Health and Medical Research Council of Australia Palliative Care Program Grant.